The effects of digitalization on gender equaliy in the G20 economies: Women20 study - Alina Sorgner; Eckhardt Bode; Christiane Krieger-Boden; Urvashi Aneja; Susan Coleman; Vidisha Mishra; Alicia M. Robb (Kiel Institute for the World Economy (IfW), 2017)
This study investigates how the digital revolution, which is characterized by artificial intelligence, big data, cloud computing and mobile robotics, will affect gender equality in G20 countries, and how governments and non-governmental initiatives may exploit the new digital technologies to narrow these gender gaps in the future. The study focuses on four areas to derive its policy recommendations. First, it assesses if digital technologies will affect gender equality in the foreseeable future by replacing women's jobs to a different extent than men's jobs. Second, it determines the state of the art in gender equality and gender-oriented policies in labor markets, financial inclusion and entrepreneurship in the G20 countries. Third, it identifies deficits in women's digital inclusion that may impair the effectiveness of digitally empowered gender policies. It also shows how digital technologies may empower women. And fourth, it provides three detailed case studies. Two case studies, coauthored by Urvashi Aneja and Vidisha Mishra, zoom deeper into the options for digitally empowered gender policies in two selected countries, India and South Africa, while the third, coauthored by Susan Coleman and Alicia Robb, highlights digitally empowered strategies for reducing the gender gap in angel investment, a promising tool for fostering female entrepreneurship...
Additional information: This study is a joint project by the Women20 and the Think Tank 20 initiatives under the German G20 presidency, supported financially by the Emerging Market Sustainability Dialogues (EMSD) and the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). This study is the final report. An executive summary has been published on occasion of the Women20 summit in Berlin.
Keywords: 330